If k#0 and k - (3 -2k^2)/k = x/k, then x = : GMAT Problem Solving (PS)
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 20 Jan 2017, 08:47

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If k#0 and k - (3 -2k^2)/k = x/k, then x =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 36582
Followers: 7086

Kudos [?]: 93259 [0], given: 10555

If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

24 Feb 2014, 22:50
Expert's post
9
This post was
BOOKMARKED
00:00

Difficulty:

35% (medium)

Question Stats:

58% (01:50) correct 42% (00:59) wrong based on 600 sessions

### HideShow timer Statistics

The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

Problem Solving
Question: 111
Category: Algebra Second-degree equations
Page: 76
Difficulty: 500

GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!
[Reveal] Spoiler: OA

_________________
Math Expert
Joined: 02 Sep 2009
Posts: 36582
Followers: 7086

Kudos [?]: 93259 [0], given: 10555

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

24 Feb 2014, 22:50
Expert's post
1
This post was
BOOKMARKED
SOLUTION

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

Multiply by k: $$k^2 - (3 -2k^2) = x$$;

$$x=3k^2-3$$.

_________________
Manager
Joined: 14 Jan 2013
Posts: 154
Concentration: Strategy, Technology
GMAT Date: 08-01-2013
GPA: 3.7
WE: Consulting (Consulting)
Followers: 3

Kudos [?]: 248 [0], given: 30

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

25 Feb 2014, 04:10
After Solving the equation , I got A
_________________

"Where are my Kudos" ............ Good Question = kudos

"Start enjoying all phases" & all Sections

__________________________________________________________________
http://gmatclub.com/forum/collection-of-articles-on-critical-reasoning-159959.html

http://gmatclub.com/forum/percentages-700-800-level-questions-130588.html

http://gmatclub.com/forum/700-to-800-level-quant-question-with-detail-soluition-143321.html

Manager
Status: GMATting
Joined: 21 Mar 2011
Posts: 108
Concentration: Strategy, Technology
GMAT 1: 590 Q45 V27
Followers: 1

Kudos [?]: 90 [1] , given: 104

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

25 Feb 2014, 22:26
1
KUDOS
k - \frac{3 -2k^2}{k} = \frac{x}{k};
After simplifying and canceling k in the denominator, we get: k^2 - 3 + 2k^2 = x;
3k^2 - 3 = x;

Ans is (C).
Senior Manager
Joined: 20 Dec 2013
Posts: 273
Location: India
Followers: 0

Kudos [?]: 81 [2] , given: 29

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

26 Feb 2014, 01:10
2
KUDOS
Option C.
k-(3-2k^2)/k=x/k
Multiply both sides by k
k^2-3+2k^2=x
3k^2-3=x
Senior Manager
Joined: 20 Dec 2013
Posts: 273
Location: India
Followers: 0

Kudos [?]: 81 [0], given: 29

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

26 Feb 2014, 01:28
Thank You for kudos,WoundedTiger!
Math Expert
Joined: 02 Sep 2009
Posts: 36582
Followers: 7086

Kudos [?]: 93259 [0], given: 10555

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

01 Mar 2014, 03:12
SOLUTION

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

Multiply by k: $$k^2 - (3 -2k^2) = x$$;

$$x=3k^2-3$$.

_________________
SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1858
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Followers: 47

Kudos [?]: 1934 [0], given: 193

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

08 Jul 2014, 21:17
Bunuel wrote:
SOLUTION

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

Multiply by k: $$k^2 - (3 -2k^2) = x$$;

$$x=3k^2-3$$.

I just added a step after the highlighted one to remove -ve sign . Rest all did same

$$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$;

$$k + \frac{2k^2 - 3}{k} = \frac{x}{k}$$
_________________

Kindly press "+1 Kudos" to appreciate

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7125
Location: Pune, India
Followers: 2137

Kudos [?]: 13666 [0], given: 222

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

08 Jul 2014, 22:55
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

You can also put in k = 1 in $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$ to get x = 0.
When you put k = 1 in options, only (C) and (E) give x = 0.

Now put k = -1 in $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$ to get x = 0.
When you put k = -1 in options, only (C) gives x = 0
_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for $199 Veritas Prep Reviews Current Student Joined: 14 Oct 2013 Posts: 48 GMAT 1: Q V Followers: 0 Kudos [?]: 6 [0], given: 120 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 19:07 Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. Verbal Forum Moderator Joined: 02 Aug 2009 Posts: 4227 Followers: 327 Kudos [?]: 3453 [1] , given: 101 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 19:28 1 This post received KUDOS Expert's post soniasawhney wrote: Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. hi soniasawhney.. it does not require any parenthesis as any sign in front of a fraction modifies the entire fraction irrespective of the term.. just an example.. let the fraction be - $$\frac{7-9}{2}$$.. two ways to do it .. first change signs first and then find answer... $$\frac{-7+9}{2}$$=$$\frac{2}{2}$$=1... second simplify and then change the signs... - $$\frac{7-9}{2}$$=- $$\frac{-2}{2}$$=-(-1)=1.. so both ways answer is same, which means parentheses is not required and a sign in front of a fraction automatically means that the entire fraction is inside bracket.... _________________ Absolute modulus :http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372 Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html Veritas Prep GMAT Instructor Joined: 16 Oct 2010 Posts: 7125 Location: Pune, India Followers: 2137 Kudos [?]: 13666 [1] , given: 222 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Mar 2015, 20:24 1 This post received KUDOS Expert's post soniasawhney wrote: Why do we automatically assume there are parentheses around (3-2k^2)? I didn't assume that so then I didn't distribute the negative on the outside which of course then gave me answer A. To clarify further: There are 3 ways in which you can make a fraction negative $$\frac{-3}{5}$$ $$-\frac{3}{5}$$ Take this to mean $$\frac{-3}{5}$$ and $$\frac{3}{-5}$$ Each one of these fractions is the same as $$\frac{-3}{5}$$ Now what happens in case you have multiple terms in numerator: $$\frac{-x + 2}{4}$$ The negative is only in front of x. $$-\frac{x+2}{4}$$ The negative is in effect, in front of the entire numerator. So this is the same as $$\frac{-(x+2)}{4}$$ _________________ Karishma Veritas Prep | GMAT Instructor My Blog Get started with Veritas Prep GMAT On Demand for$199

Veritas Prep Reviews

Manager
Joined: 27 Jun 2014
Posts: 78
Location: New Zealand
Concentration: Strategy, General Management
GMAT 1: 710 Q43 V45
GRE 1: 324 Q161 V163
GRE 2: 325 Q159 V166
GPA: 3.6
WE: Editorial and Writing (Computer Software)
Followers: 4

Kudos [?]: 44 [0], given: 125

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

12 Mar 2015, 18:40
Mountain14 wrote:
After Solving the equation , I got A

Because you didn't distribute the first negative sign on the first fraction. I made the same mistake. 8th grade rules but still find them hard to remember.
_________________

"Hardwork is the easiest way to success." - Aviram

One more shot at the GMAT...aiming for a more balanced score.

Optimus Prep Instructor
Joined: 06 Nov 2014
Posts: 1782
Followers: 51

Kudos [?]: 393 [0], given: 21

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

12 Mar 2015, 22:12
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

If $$k\neq{0}$$ and $$k - \frac{3 -2k^2}{k} = \frac{x}{k}$$, then x =

(A) -3 - k^2
(B) k^2 -3
(C) 3k^2 - 3
(D) k - 3 - 2k^2
(E) k - 3 + 2k^2

Problem Solving
Question: 111
Category: Algebra Second-degree equations
Page: 76
Difficulty: 500

GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!

Given that,
k - (3 - 2k^2)/k = x/k
Take LCM of denominators,
So, [k^2 - (3 - 2k^2)]/k = x/k
So, [k^2 - 3 + 2k^2]/k = x/k
Canceling out k from the denominators of both sides,
So, [k^2 - 3 + 2k^2] = x
So, 3k^2 - 3 = x
Hence option C.

--
Optimus Prep's GMAT On Demand course for only $299 covers all verbal and quant. concepts in detail. Visit the following link to get your 7 days free trial account: http://www.optimus-prep.com/gmat-on-demand-course _________________ # Janielle Williams Customer Support Special Offer:$80-100/hr. Online Private Tutoring
GMAT On Demand Course $299 Free Online Trial Hour Veritas Prep GMAT Instructor Joined: 16 Oct 2010 Posts: 7125 Location: Pune, India Followers: 2137 Kudos [?]: 13666 [1] , given: 222 Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink] ### Show Tags 10 Apr 2016, 22:10 1 This post received KUDOS Expert's post Apollon wrote: I'm not sure whats wrong here: 1. k - [3-2k^2][/k] = [x][/k] 2. k - 3 + 2k^2 = x I am assuming I can't move the denominator to the right side because of the first term (k), just not sure why. Yes, you re right. To move the denominator to the other side, it must be the denominator of the entire expression. Look at it from a very basic viewpoint: 1/2 = x 1 = 2x Since x is 1/2, twice of x will be 1. 1 + 1/2 = x 1 + 1 = 2x ???? x is actually 3/2 or (1.5). If you double it, will you get 2? No. On the other hand, (1 + 3+ 5)/2 = x Then (1 + 3 + 5) = 2x is correct. _________________ Karishma Veritas Prep | GMAT Instructor My Blog Get started with Veritas Prep GMAT On Demand for$199

Veritas Prep Reviews

Intern
Joined: 31 Oct 2013
Posts: 4
Followers: 0

Kudos [?]: 0 [0], given: 2

Re: If k#0 and k - (3 -2k^2)/k = x/k, then x = [#permalink]

### Show Tags

18 Apr 2016, 05:31
I get it. Thank you for both of the explanations!
Re: If k#0 and k - (3 -2k^2)/k = x/k, then x =   [#permalink] 18 Apr 2016, 05:31
Similar topics Replies Last post
Similar
Topics:
If k#0, and z^2/k +4z+3 = z/k, then, k=? 2 13 Feb 2016, 03:59
3 If k ≠ 0, k ≠ ±1, and (k^3*k*k^4)^2/k^n*k=k^14 , then n = 5 01 Apr 2015, 03:09
4 If f(x) = 12 - x^2/2 and f(2k) = 2k, what is one possible value for k? 5 19 Mar 2015, 05:26
103 If x is an integer then x(x-1)(x-k) must be evenly divisible 22 31 Jan 2012, 14:49
4 If one root of the equation 2x^2 + 3x – k = 0 is 6, what is the value 6 17 Apr 2011, 08:17
Display posts from previous: Sort by